2018
DOI: 10.1038/s41598-018-19696-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping and genomic prediction for CBSD resistance in Manihot esculenta

Abstract: Cassava (Manihot esculenta Crantz) is an important security crop that faces severe yield loses due to cassava brown streak disease (CBSD). Motivated by the slow progress of conventional breeding, genetic improvement of cassava is undergoing rapid change due to the implementation of quantitative trait loci mapping, Genome-wide association mapping (GWAS), and genomic selection (GS). In this study, two breeding panels were genotyped for SNP markers using genotyping by sequencing and phenotyped for foliar and CBSD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 78 publications
17
77
0
Order By: Relevance
“…The broad-sense heritability estimates for CBSD in the present study were comparable with heritability estimates previously reported (Kayondo et al, 2018), ranging from 0.25 for CBSDRs to 0.61 for CBSD3s, from the genome-wide association study involving ?1300 clones evaluated across five sites in Uganda. The broad-sense heritability estimates for CBSD in the present study were comparable with heritability estimates previously reported (Kayondo et al, 2018), ranging from 0.25 for CBSDRs to 0.61 for CBSD3s, from the genome-wide association study involving ?1300 clones evaluated across five sites in Uganda.…”
Section: Heritability Estimates and Mean Gebvs Of C 1 And C 0 Clonessupporting
confidence: 90%
See 2 more Smart Citations
“…The broad-sense heritability estimates for CBSD in the present study were comparable with heritability estimates previously reported (Kayondo et al, 2018), ranging from 0.25 for CBSDRs to 0.61 for CBSD3s, from the genome-wide association study involving ?1300 clones evaluated across five sites in Uganda. The broad-sense heritability estimates for CBSD in the present study were comparable with heritability estimates previously reported (Kayondo et al, 2018), ranging from 0.25 for CBSDRs to 0.61 for CBSD3s, from the genome-wide association study involving ?1300 clones evaluated across five sites in Uganda.…”
Section: Heritability Estimates and Mean Gebvs Of C 1 And C 0 Clonessupporting
confidence: 90%
“…Moderate to high estimates of broad-sense heritability for foliar and root severities were registered for CBSD (ranging from 0.26 to 0.70) in both populations studied here. The broad-sense heritability estimates for CBSD in the present study were comparable with heritability estimates previously reported (Kayondo et al, 2018), ranging from 0.25 for CBSDRs to 0.61 for CBSD3s, from the genome-wide association study involving ?1300 clones evaluated across five sites in Uganda. These moderate to high broad-sense heritability estimates for CBSD indicated that selection efficiency either through conventional or GS would be high enough to achieve the desired genetic gains.…”
Section: Heritability Estimates and Mean Gebvs Of C 1 And C 0 Clonessupporting
confidence: 90%
See 1 more Smart Citation
“…() showcased the method's power for mapping natural genetic variants for more than 100 traits in A. thaliana . To date, GWAS have also identified the genetic basis of numerous agronomic traits, speeding up breeding programs of crops such as maize (Jiao et al ., ; Zila et al ., ; Wallace et al ., ; Hu et al ., ; Xu et al ., ) and rice (Huang et al ., , ; McCouch et al ., ; Wang et al ., ; Wang et al ., ), as well as crops with less well‐developed molecular resources such as wheat (Liu et al ., ; Kristensen et al ., ), soybean (Fang et al ., ), barley (Sharma et al ., ), cotton (Fang et al ., ; Du et al ., ), cassava (Kayondo et al ., ), foxtail millet (Jia et al ., ), spinach (Ma et al ., ) and cauliflower (Thorwarth et al ., ). GWAS are a particularly relevant tool for perennial species such as apple (Urrestarazu et al ., ), citrus (Minamikawa et al ., ), eucalyptus (Resende et al ., ) and poplar (Liu et al ., ).…”
Section: Finding Associations Between Genotype and Phenotype: Linkagementioning
confidence: 99%
“…Because cassava is an outcrossing species mostly 87 propagated by stem cuttings, conventional breeding methods can take more than five years to 88 produce superior performing clones (www.nextgencassava.org). Genome-wide association 89 studies (GWAS) are complementary to GS as they have proven effective for the identification 90 of QTL regions associated with several traits that are critical for cassava breeding, including 91 cassava mosaic disease resistance (CMD) (Wolfe et al, 2016), cassava brown streak disease 92 resistance (CBSD) (Kayondo et al, 2018), and beta-carotene content and dry matter content 93 (Rabbi et al, 2017). 94 95 In this study, size and shape related traits describing cassava roots were obtained through 96 automated image analysis.…”
mentioning
confidence: 99%